Are the factors of adolescents taking-up smoking and vaping the same? - Nurulhuda, M.H.; Abd Aziz, A.; Norwati, D.; Juhari, S.N.; Mazubir, N.N. (2021)
Smoking remains one of the hazardous acts to health, which is important to prevent in adolescents. Nowadays vaping has also became a worrying trend with similar hazards. Are the factors of adolescents taking-up smoking and vaping the same? This study compares the associated factors of smoking and vaping among school-going adolescents in Terengganu, Malaysia. This cross-sectional study was done from December 2018 to September 2019. A validated questionnaire adapted from Global School Health Survey (GSHS) was administered to 732 school-going adolescents aged 13 to 18 years old. Secondary schools and classes were selected using cluster random sampling. Data were analyzed using SPSS ver23, using multiple logistic regression for both dependent variables of smoking and vape. Independent variables include age, gender, race, family income, parents’ marital status, and family members smoking. More students (22%) had tried vape, compared to smoking (13.2%). Majority (54%) of those who tried vape were virgin vaper, who had never tried smoking. Vaping was significantly associated with increase age (p<0.001,OR:1.54,CI:1.34,1.79), male gender(p<0.001,OR:9.92,CI:6.11,16.12), parents’ marital status (p=0.005,OR: 2.57,CI:1.34,4.94) and family members smoking (p=0.003,OR:1.11,CI:1.04,1.19). Smoking was significantly associated with increase age, male gender, poorer family income and family members smoking. In conclusion, vaping is an emerging worrying trend among adolescents, with some similar significant associated factors with smoking, but majority had never tried smoking before. A dual-target approach should be taken to curb the initiation of both smoking and vaping as there is a similar target population and there should be more emphasis towards education regarding the dangers of vaping among adolescents.